Respuesta :
Answer:
- x = -7
- y = -9
Step-by-step explanation:
- -3x + 4y = -15
4x - y = -19
- => -3x + 4y = -15
4(4x - y) = 4(-19)
- => -3x + 4y = -15
16x - 4y = -76
- => 13x = -91
- => x = -7
Now, let's substitute the 'x' value in the equation.
- => -3(-7) + 4y = -15
- => 21 + 4y = -15
- => 4y = -21 - 15
- => 4y = -36
- => y = -9
Conclusion:
Therefore, the answers are:
- x = -7
- y = -9
Hoped this helped.
[tex]BrainiacUser1357[/tex]
Answer:
(-7, -9).
( x = -7 and y = -9)
Step-by-step explanation:
-3x + 4y = -15
4x - y = -19
Multiply second equation by 4:
16x - 4y = -76
Add this equation to the first to eliminate y:
13x = -15 + -76
13x = -91
x = -7.
Substitute this into equation 2:
4(-7) - y = -19
-y = -19 + 28
-y = 9
y = -9.